(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study examines how fish farmers in India can efficiently address issues with food safety requirements by implementing a problem-based learning (PBL) method. This paper further demonstrates the potential of PBL to foster the skills required to train various stakeholders, including employees of local, district, and national organizations, and to help local fish farmers implement the FAO Food Safety Code of Practice on their farms, using the example of a Food and Agriculture Organization (FAO) Food Safety Program. To evaluate and give a detailed account of the PBL program, the prospective capacities produced, and the impact(s) of the project, a qualitative intrinsic case study technique was used in conjunction with qualitative content analysis of written reports. Using a cascade model of training, the PBL approach used to train numerous stakeholders was founded on the social constructivism teaching and learning theory. Based on these ideas, the training has improved fish farmers’ business quality and performance as well as food safety control, encouraged capacity building at the various cascade model levels, and given them the authority to modify their behavior and embrace the FAO Food Safety Code of Practice. Additionally, the training program’s effectiveness allowed it to be expanded to an additional 100,000 fish farms, and other farm types, including crop and poultry farms, have also adopted the same strategy. By forming cooperative relationships with various actors in the fishing industry, this article clearly explains how a PBL approach can surpass capacity building and increase sustained effect while bringing about beneficial changes in the communities they assist.